The Development of Google Sites-Based Social Studies Learning Media on ASEAN Material to Enhance Students’ Critical Thinking Skills - Fatoni, Satria Fajar; Nikmah, Khoirun (Edukasi IPS, 2025)
This research aims to develop a Google Sites-based learning media for Social Studies, specifically targeting ASEAN material, and to assess its effectiveness in enhancing students' critical thinking skills at MTsN 2 Ponorogo. The study was conducted as a Research and Development (R&D) project using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, interviews, and questionnaires, with validations from media and content experts. Results showed that the developed media was highly feasible, receiving an 85% score from content experts and 87% from media experts. The media received very positive feedback from both teachers (90%) and students (82.88%). Pretest and posttest comparisons revealed a significant improvement in students' critical thinking skills, supported by a T-test (p = 0.000 < 0.05) and an N-Gain score of 60.24%, classified as moderately effective. These findings suggest that Google Sites-based media is a valid and effective tool to enhance critical thinking in Social Studies education.